Answer:
( 0,0) and (3,0)
Step-by-step explanation:
y=(2x(x-3))/(x-1)
Set y = 0
0 =(2x(x-3))/(x-1)
Multiply each side by x-1, which makes x not equal to 1
0 =(2x(x-3))
Using the zero product property
2x=0 x-3 =0
x=0 x= 3
The x intercepts are x=0 x= 3
( 0,0) and (3,0)
Answer:it’s 0
Step-by-step explanation:
You do -3 plus 4 and then minus 1 which would be 0
Answer: x = 3.4
Step-by-step explanation: took the test and got it right. if you need help on this kind of work u can use things like (graphing gens) or math to help you more.
Angle bisector would be the answer